2018
DOI: 10.1021/acs.chemrestox.7b00293
|View full text |Cite
|
Sign up to set email alerts
|

Role of Glucuronidation and P450 Oxidation in the Bioactivation of Bromfenac

Abstract: Bromfenac is a nonsteroidal anti-inflammatory drug that was approved in the United States in 1997. It was withdrawn from clinical use less than one year later, in 1998, due to hepatotoxicity. We investigate the potential of bromfenac to be metabolized to reactive intermediates to further the current understanding of bromfenac bioactivation. Incubations were conducted with hepatocytes and human, rat, and cynomolgus liver microsomes fortified with cofactors and N-acetylcysteine. One thioether adduct of hydroxyla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 27 publications
3
19
0
Order By: Relevance
“…Therefore, in order to predict the toxicological risk of AGs more accurately, the contribution of the other metabolizing enzymes (such as CYP) and drug transporters should be considered. For example, it was reported that the bioactivation of bromfenac and diclofenac is involved in not only UGT but also CYP. In addition, we found that Cys can trap AG as a “hard” electrophile and evaluate AG reactivity. It is proposed that not only a “soft” thiol group but also a “hard” amino group of Cys can play important roles in trapping AG through acylation during amide adduct formation.…”
Section: Discussionmentioning
confidence: 78%
“…Therefore, in order to predict the toxicological risk of AGs more accurately, the contribution of the other metabolizing enzymes (such as CYP) and drug transporters should be considered. For example, it was reported that the bioactivation of bromfenac and diclofenac is involved in not only UGT but also CYP. In addition, we found that Cys can trap AG as a “hard” electrophile and evaluate AG reactivity. It is proposed that not only a “soft” thiol group but also a “hard” amino group of Cys can play important roles in trapping AG through acylation during amide adduct formation.…”
Section: Discussionmentioning
confidence: 78%
“…Rosuvastatin was used as a positive control in our in‐house assay and the data aligned with our historical data. As previously published, the major routes of elimination for bromfenac were glucuronidation and P450 oxidation 22 ; therefore bromfenac was not assayed in SCCH.…”
Section: Resultsmentioning
confidence: 99%
“…Biliary clearance was assumed to be the major route of elimination for rosuvastatin and carotegrast, 20,21 whereas metabolism in the liver was assumed to be the major pathway of elimination for bromfenac 22 in the model fitting. Urinary excretion of rosuvastatin in monkeys was reported to be ~ 20% of the absorbed dose 12,23 .…”
Section: Methodsmentioning
confidence: 99%
“…Observed symptoms of toxicity included increases in liver transaminase levels, hepatic necrosis, cholestasis, and fatal liver failure. While the mechanism of hepatotoxicity remains unclear for bromfenac, there is evidence for the formation of reactive metabolites . Reactive metabolites are capable of covalently binding to and modifying biological matrices resulting in species that are not recognized by the body as self and can result in an immune response .…”
Section: Introductionmentioning
confidence: 99%
“…The bioactivation of bromfenac and its metabolites was recently proposed . In the metabolic pathway, one step is a uridine 5′-diphospho-glucuronosyltransferase (UGT) catalyzed conversion of bromfenac to an internally cyclized indolinone metabolite in human liver microsomes (HLM) in the presence of UDPGA.…”
Section: Introductionmentioning
confidence: 99%